Respuesta :
Property of inverse functions:
[tex]f(f^{-1}(x)) = x \\ \\ f^{-1}(f(x)) = x[/tex]
Therefore the answer to both is True.
[tex]f(f^{-1}(x)) = x \\ \\ f^{-1}(f(x)) = x[/tex]
Therefore the answer to both is True.
Answer:
True
Step-by-step explanation:
Given : Expression [tex]\csc^{-1}[\csc(-\frac{\pi}{4})]=-\frac{\pi}{4}[/tex] and [tex]\sec[{\sec^-1}(\sqrt3)]=\sqrt3[/tex]
To find: The given expression are true or false?
Solution :
In the given expression,
Applying Inverse trigonometric functions,
i.e, [tex]f(f^{-1}x)=x[/tex]
or [tex]\csc^{-1} (\csc x)=x\\\csc(\csc^{-1} x)=x[/tex]
and this true for all trigonometric functions.
So, if apply in the given expression the resultant we get is true.
[tex]\csc^{-1}[\csc(-\frac{\pi}{4})]=-\frac{\pi}{4}[/tex] is true
and [tex]\sec[{\sec^-1}(\sqrt3)]=\sqrt3[/tex] is true
Therefore, The given expressions are true.